KERJASAMA HOLDING PTPN III PERSERO DAN PERUSAHAAN STARBUCKS DALAM EKSPOR TEH - Fadilla Awalia; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Indonesia is one of the tea producing countries and is the world's tea producer. Tea is one of the non-oil and gas commodities that continues to grow and produces a sector that can be exported. Tea export activities between the two countries result in economic and trade cooperation. The trade war between the United States and China provided a great opportunity for Indonesia to export tea, one of which was the export of tea by the State-Owned Enterprise Holding PTPN III Persero with the American beverage company Starbucks Corporation. Based on these conditions, this paper discusses why Holding PTPN III Persero exports tea to Starbucks Company.. In this study, the authors obtained data from primary sources or primary data in the form of interview results, data through literacy such as books, journals, articles, web pages, and official e-mails. This study uses the level of group analysis, where the subjects are several agency groups. The method used in this study is a qualitative explanatory method. Qualitative research is research that intends to understand the phenomenon of what is experienced by the research object. Explanative qualitative describes different social phenomena and is explained with an overview that is the main explanation. The results of this study indicate that tea export activities between Holding PTPN III Persero and Starbucks are part of the PTPN Holding's mission to increase direct sales to companies that directly process tea produced by PTPN as a raw material for beverages. These exports generate several economic benefits, namely increasing the country's foreign exchange, expanding the market area, increasing production, and modernizing technology. This collaboration allows Indonesian tea to compete with the quality of other international tea products. Keywords : Export, Tea, Coorperations, Holding PTPN, Starbucks